Multiphysics to Investigate the Thermal and Mechanical Responses in Hard Disk Drive Components Due to the Reflow Soldering Process - Kimaporn, Napatsorn; Samakkarn, Chawit; Thongsri, Jatuporn (My University, 2024)
In hard disk drive (HDD) manufacturing, a reflow soldering process (RSP) implements heat generated by the welding tip to melt a solder ball for bonding the following essential HDD components: a flexible printed circuit (FPC) and a printed circuit cable (PCC). Since the mentioned components are tiny and comprise many thin material layers, an experiment to study thermal and mechanical responses is complex and not worth it. Therefore, a static state multiphysics consisting of thermal analysis (TA) and structural analysis (SA) was employed to investigate both responses. First, the experiment was established to mimic the RSP, measuring the temperature generated by the actual welding tip. Then, the measured temperature was defined as the boundary conditions with the pressing force (F) for the TA and SA based on the actual operating conditions. As expected, the TA results revealed the temperature distribution in the HDD components, which was consistent with the theory and results from previous work and confirmed this work’s credibility. Significantly, the SA reported severe total deformation (δ) in FPC’s top and bottom ends. The maximum δ was 0.72–0.88 mm for the F of 0–1 N. The stronger the F, the greater the δ. This research highlights that multiphysics can investigate both responses in HDD components as slight as 0.1–100 microns thick, which can be used to develop a high-efficacy RSP.
Keywords: finite element analysis; hard disk drive; heat transfer; multiphysics; reflow soldering process; structural analysis; thermal analysis